At the Crossroads between the East and West : the Yugoslav Legacy in Serbian Foreign Relations - Madić, Maša; Hennlichová, Marcela; Kočí, Kateřina; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
Serbia is a small nation at the crossroads of the Eurasian West and East, where the EU and Russia as political giants each stake their own interests and needs. Neither, therefore, fully prioritise Serbian foreign policy aims, leading the Balkan nation to engage in dialogue with either and both sides from the position of a small power seeking neutrality. To analyse how exactly such balancing occurs in the realms of political and economic diplomacy, i.e. soft power – as well as seeking to determine the existence of a continuity in such a foreign practice across two Serbian political identities - the Bachelor Thesis aims to analyse Yugoslavia’s relations with Western Europe (including the CoE & EEC) and the USSR in the 1960-1980s grounded in non-alignment, as well as Serbia’s relations with the EU and the Russia in 2000-2020s.
Vedoucí práce: Marcela Hennlichová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor bakal. práce]; bakalářské práce; bachelor's theses